Sistem Informasi Donor Darah Berbasis Web Menggunakan Framework CodeIgniter Pada Unit Transfusi Darah Palang Merah Indonesia (UTD PMI) Lumajang - Iqbal Ramadhani Mukhlis (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
In this pandemic era, many people who need blood often have difficulty when looking for information on blood supplies. This is because the Indonesian Red Cross (PMI) or the Blood Transfusion Unit (UTD) do not yet have a donor database that can be accessed quickly. It is necessary to find a way to solve existing problems by providing an information system program for blood donor services that can be accessed by the public. The web-based Blood Donor Information System is a way to display a web page. An online blood donor information system is hoped that people who need blood donor information can access the information created. With this information system that uses PHP programming technology and a MySQL database with the support of the CodeIgniter framework, it can make it easier for the public to access a web-based blood donors information system. Based on the results of research conducted using internal and external tests obtained a value of 75% which can be concluded that the information system can be used to identify blood donors in Lumajang Regency which is managed by the Indonesian Red Cross Blood Transfusion Unit (UTD PMI) Branch Lumajang online.